Tortura e violência doméstica: uma análise da abrangência das condutas qualificadas como tortura à luz da dignidade da pessoa humana - Castro, Wellington Clair de (2019)
This thesis aims to demonstrate that the legislator, by failing to predict as torture the crime of domestic and family violence against women and by dedicating a milder treatment to this kind of violence, currently creates a barrier in the fight for reduction of this criminal modality in the country. The study suggests a change in the law on torture to include, albeit in a supplementary way, acts of domestic and family violence that would cause physical and psychological distress to victims. During the course of this investigation, it is shown that among the roles of law, what better generates hope in society is the achievement of justice. From the recognition of human dignity as an intrinsic value to the human being, social movements have been reporting the conditions of subordination and subjection of women, leading to the break of silence that used to be customary in this type of violence. The study concludes that the State does not appropriately foster, either by legal or administrative means, suitable measures to adequately address domestic violence. This has been, therefore, the cause of its growth and recurrence. This is a demonstration of the intentional omission of the legislator in guaranteeing women the due protection for their emancipation. The absence of egalitarian legal provision in this type of behavior encourages the recidivism of crimes of domestic and family violence. An alternative solution, as proposed in this study, is to treat domestic and family violence against women as a kind of torture, punishing more rigorously the perpetrator in order to reduce violence within the family and promote equal treatment of genders so celebrated by human dignity